Environmental chemicals desk reference - Montgomery, John H. 1955-; Crompton, T. R. (CRC Press, Taylor & Francis Group, 2018)
"Environmental Chemicals Desk Reference is a concise version of the widely read Agrochemicals Desk Reference and Groundwater Chemicals Desk Reference."--Page 4 of cover.